Los procesos de atención en el departamento de cobro y su incidencia con el cumplimiento de obligaciones tributarias - Robalino Pérez, María Verónica (2017)
The objective of this study was to investigate how dividend taxation affects the double taxation of Income Tax in Ecuador, taking as reference international taxation, mechanisms to avoid double taxation and domestic legislation. Dividend treatment in its understanding and application is complex for taxpayers, even for the tax administration itself, which may affect the taxpayer financially, since double taxation can be applied in their application. Hence, it is necessary to have models that base their application on a Simple Tax Regime, efficient, that allows a correct determination of Income Tax generated by dividends, which serve even as an input for the control processes carried out by the Administration Tax.